REQUALIFICAÇÃO DO CASTELINHO E DO SEU ENTORNO IMEDIATO - PONTA PORÃ-MS. - Silva, Eduardo Roberto Melo da (2018)
Built in 1927, the Castelinho, located in the center of the city of Ponta Porã-MS, is a copy that has cultural value for the South-Matogrossense people, as it is a building representative of the occupation of the southern portion of the State, with relations intrinsic to the history of the border, permeated by land conflicts and the Economic Cycle of the Mate herb occurred in the region between the period of 1883-1947. In addition, its construction for military purposes can be considered as an important aspect in the development of the city of Ponta Porã, which, associated with the arrival of the railroad and its equipment, such as the station and the village of the railwaymen in its vicinity, among the years from 1940 to 1950, formed an important pole for the security, control and inspection of the border, providing part of the development of the city and occupation around these structures. Currently, the current situation is one of enormous degradation of the Castelinho, mainly due to the inexistence of use, associated to an urban dynamic in its surroundings, which has been formed in a disorderly way after the extinction of railway activities in the mid 2000s, a situation that directly affects the reading of the representative buildings and the area in which they are inserted as historical nucleus. Considering that these buildings, the Castelinho and the remaining railways, were dropped between 1997 and 2008, it is necessary to preserve and perceive these monuments, therefore, to recover the Castelinho and to help in the possibility of its use and intervene in its immediate environment is the general objective to be fulfilled in order to better understand, value and enhance the historical nucleus formed, respecting the current consolidated dynamics of the area. Thus, the present work as project intervention the "Requalification of the Castle and its Immediate Surroundings"